Monitoring AKT activity and targeting in live tissue and disease contexts using a real-time Akt-FRET biosensor mouse - Conway James R.W.; Warren Sean C.; Lee Young-Kyung; Mcculloch Andrew T.; Magenau Astrid; Lee Victoria; Metcalf Xanthe L.; Stoehr Janett; Haigh Katharina; Abdulkhalek Lea; Guaman Cristian S.; Reed Daniel A.; et al. (AMER ASSOC ADVANCEMENT SCIENCE, 2025)
Aberrant AKT activation occurs in a number of cancers, metabolic syndrome, and immune disorders, making it an important target for the treatment of many diseases. To monitor spatial and temporal AKT activity in a live setting, we generated an Akt-FRET biosensor mouse that allows longitudinal assessment of AKT activity using intravital imaging in conjunction with image stabilization and optical window technology. We demonstrate the sensitivity of the Akt-FRET biosensor mouse using various cancer models and verify its suitability to monitor response to drug targeting in spheroid and organotypic models. We also show that the dynamics of AKT acti-vation can be monitored in real time in diverse tissues, including in individual islets of the pancreas, in the brown and white adipose tissue, and in the skeletal muscle. Thus, the Akt-FRET biosensor mouse provides an important tool to study AKT dynamics in live tissue contexts and has broad preclinical applications.